A single‐centre, prospective cohort study of COVID‐19 patients admitted to ICU for mechanical ventilatory support. Issue 3 (22nd November 2020) - Søvik, Signe; Bådstøløkken, Per M.; Sørensen, Vibecke; Myhre, Peder Langeland; Prebensen, Christian; Omland, Torbjørn; Berdal, Jan‐Erik
Abstract : Background: Mortality rates in COVID‐19 patients in need of mechanical ventilation are high, with wide variations between countries. Most studies were retrospective, and results may not be generalizable due to differences in demographics, healthcare organization and surge capacity. We present a cohort of mechanically ventilated COVID‐19 patients from a resource‐rich, publicly financed healthcare system. Methods: Prospective study from a tertiary hospital. Consecutive SARS‐CoV‐2 positive adult patients admitted to the ICU for mechanical ventilation from 10 March 2020 to 04 May 2020 were included. Triage and treatment were protocolized. High‐dose dalteparin was adjusted by D‐dimer. Demographics, treatments and high‐resolution physiological variables were collected. Outcomes were 30‐day and hospital mortality. Data are medians (quartiles). Results: Of the 1484 persons in the hospital catchment area testing positive for SARS‐CoV‐2, 201 (13.5%) were hospitalized. Thirty‐eight (19%) patients were mechanically ventilated, of whom five (13%) died. Of the 163 patients treated with supplemental oxygen, eight (5%) died. In ventilated patients (75% males, age 61 (53‐70) years), severe, moderate and mild ARDS was present in 25%, 70% and 5%. Tidal volume ≤8 mL/kg ideal bodyweight was achieved in 34 (94%) patients. Proning and neuromuscular blockers were used in 19 (54%) and 20 (61%) patients. Duration of ventilation was 12 days (8‐23). D‐dimer peaked at 3.8 mg/L (2.1‐5.3), and maximum dalteparin dose was 15 000 IU/24 h (10 000‐15 000). Despite organizational changes, a high degree of adherence to treatment protocols was achieved. Conclusion: In a prospective cohort study of mechanically ventilated COVID‐19 patients treated in a resource‐rich, publicly financed healthcare system, mortality was considerably lower than previously reported in retrospective studies.